Treatment of Facial Fractures at Safety-Net Hospitals: A National Analysis of Inpatient Burden and Cost. Issue 4 (23rd June 2021) - Musavi, Leila S.; Chin, Patrick; Pfaff, Miles; Fadavi, Darya; Aliu, Oluseyi; Yang, Robin
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose: Safety-net hospitals (SNHs) are vital in the care of trauma populations, but little is known about the burden of facial trauma presenting to SNHs. The authors sought to characterize the presentation and treatment of facial fractures across SNHs and determine the association between SNH care and healthcare utilization in patients undergoing fracture repair. Methods: Adult patients presenting with a facial fracture as their primary admitting diagnosis from the year 2012 to 2015 were identified in the National Inpatient Sample. The "safety-net burden" of each hospital was defined based on the proportion of Medicaid and self-pay discharges. Patient factors analyzed were sex, race, age, income level, insurance status, fracture location, and comorbidities. Hospital factors analyzed were safety-net burden, teaching status, geographic region, bed size, and ownership status. The main outcomes were length of stay (LOS), hospital costs, time to repair, and postoperative complications. Results: Of 78, 730 patients, 27, 080 (34.4%) were treated at SNHs and 24, 844 (31.6%) were treated at non-SNHs. Compared to non-SNHs, patients treated at SNHs were more likely to undergo operative repair at SNHs (65.8% versus 53.9%, P < 0.001). Overall mean LOS was comparable between non-SNH and SNH (3.43 versus 3.38 days, P = 0.611), as was mean hospital cost (15, 487 versus 15, 169, P = 0.434). On multivariate linear regression, safety-net status was not a predictor of increased LOS, cost, or complications. However, safety-net status was significantly associated with lower odds of undergoing repair within 48 hours of admission (odds ratio 0.783, 95% confidence interval = 0.680–0.900, P = 0.001). Conclusions: Safety-net hospitals are able to treat facial trauma patients with greater injury burden and lower socioeconomic resources without increased healthcare utilization. Healthcare reform must address the financial challenges that endanger these institutions to ensure timely treatment of all patients.